Curriculum, scientific epistemological views and student achievement and attitude in high school chemistry - Baliton, Maria Luisa Bernal (2005)
In this study, the Scientific Epistemological Views (SEVs) of the students and their teachers were identified, and correlated SEVs with students' achievement in high school chemistry and student's attitude toward chemistry. Students SEVs were found to have significant relationships with teachers SEVs. The students' SEVs are also significantly related to the students' performance in the Chemistry Achievement Test (CAT) and Students' Attitude in Chemistry. All components of the students' achievement were significantly related with teachers' SEVs except for laboratory skills. All components of students' attitude were not significantly related with teachers' SEVs. In terms of CAT performance of students, those who had non-traditional SEVs had significantly higher scores than those who had traditional SEVs. And, there was no significant difference between students' and teachers' SEVs except for the non-traditional and traditional scientific method categories.
"March 2005."
Thesis (M.A. Chemistry Education)--University of the Philippines, Diliman.
Keywords: Chemistry -- Study and teaching (Secondary) -- Philippines; Academic achievement -- Philippines; High school students -- Philippines -- Attitudes; Chemistry teachers -- Philippines